2021
DOI: 10.1111/hae.14280
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of joint damage and disease activity in adult patients with severe haemophilia A using the HEAD‐US system

Abstract: Introduction The Haemophilia Early Arthropathy Detection with Ultrasound (HEAD‐US) system and scoring scale has proven to be an accurate and time‐efficient imaging method for identifying joint damage in patients with haemophilia. Aim Observational, multicentre, cross‐sectional study conducted in 8 centres in Spain that assessed the joint status of adult patients with severe haemophilia A (SHA) using HEAD‐US. Methods Joint status of the elbow, knee and ankle was evaluated in adults with SHA receiving on‐demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Our work shows that 44% of PWH showed synovial hypertrophy in at least one of their joints, with the rate higher in those on tertiary or on‐demand prophylaxis and lower in those on primary prophylaxis. These findings are aligned with those published by Jimenez‐Yuste et al 25,26 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our work shows that 44% of PWH showed synovial hypertrophy in at least one of their joints, with the rate higher in those on tertiary or on‐demand prophylaxis and lower in those on primary prophylaxis. These findings are aligned with those published by Jimenez‐Yuste et al 25,26 …”
Section: Discussionsupporting
confidence: 92%
“…This difference could be due to the fact that the elbow is a less weight‐bearing joint, where synovitis is lodged in the posterior recesses of the deep olecranon fossa or in the anterior recesses under a thick muscle mass. Furthermore, several studies have already shown that in haemophilia, the elbows are affected as much as the knees and ankles 25,26 . Therefore, physical and ultrasound examination protocols should also assess this joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we report unpublished findings of a 28-adult male patient subset with moderate (n = 14) and mild (n = 14) HA, with median age of 42.5 [IQR 32-60.5] years (40.5 [IQR 30.0-49.0] and 51.0 [IQR 34.0-63.0] years for moderate and mild, respectively) from a previously performed cross-sectional study to assess joint status in Spain. 6 Not surprisingly we found 19 patients non-subjected to any evaluation by imaging modalities over the last 12 months (85.7% mild; 53.8% moderate), and also a HEAD-US score of 0 in all joints in 5 (35.7%) and 3 (21.4%) patients with mild and moderate HA, respectively. However, we observed 8 patients with target joint in at least one joint, being the ankles the most affected ones (4 patients), and total knee replacement was present in 1 mild patient (RK) and 1 moderate patient (LK).…”
mentioning
confidence: 70%
“…A substantial number of OD patients scored 0 for each evaluated joint (57.1% to 72.7%), which, as observed in severe HA patients, may implicate a significant association between arthropathy and treatment modality, with worse results in patients with OD treatments. 6,8 Severe synovitis was only observed for 1 LK and 1 LA in the OD population, although that patients on TP were poorly controlled prior to the establishment of the prophylactic regimen and had a joint status already compromised.…”
Section: Signs Of Cartilage and Bone Degeneration At Different Degreesmentioning
confidence: 96%